First record of Toxodontidae (Mammalia, Notoungulata) from the late Miocene - Early Pliocene of the southern central Andes, NW Argentina - Bonini, Ricardo Adolfo (2017)
A new species of toxodontid notoungulate, Xotodon maimarensis n. sp., is described from the Maimará Formation (late Miocene - early Pliocene), Jujuy Province, northwestern Argentina. This is the first record of a toxodontid from the Eastern Cordillera. The specimen is housed at the Museo de Geología, Mineralogía y Paleontología, Instituto de Geología y Minería de la Universidad Nacional de Jujuy. It consists of an incomplete mandible preserving the right mandibular ramus with part of the dental series, partially preserved symphysis with all the incisors, and a small portion of the left ramus without teeth. The following characters distinguish it as a new taxon: symphysis long and narrow with slight divergence of its lateral borders; strong procumbence of lower incisors and deeply implanted i3; chin angle lower than in X. major and X. cristatus and bulging labial keel limiting strong lateral concavities. Comparative analysis in the context of the recently revised Neogene Toxodontidae indicates that the Maimará specimen shares mandibular features and dental characters with Xotodon and Mixotoxodon, differing from the latter by the more upraised symphysis. The phylogenetic position of Xotodon maimarensis n. sp. supports the taxonomic interpretation of the studied specimen as a new species of Xotodon. This new Toxodontidae increases the knowledge of the diversity and radiation of this group of notoungulates in northwest Argentina.